Abelhas melíferas compondo paisagens em ruínas: o que é possível (re)existir em uma educação no Antropoceno? - Borges, Nicole Cristina Machado (2021)
We live in an era marked by mass destruction, accelerated climate change, indiscriminate use of pesticides, burning and deforestation of forests, the Anthropocene that destroys, while allowing the emergence of other lives. Amid the ruined landscapes this work emerges to rethink biology, to connect it with philosophy, politics and multispecies studies and to contribute to discussions about the Anthropocene. Starting from the thoughts of Deleuze and Guattari with the philosophy of difference, we use cartography as a power to rethink biological knowledge, meeting multispecies studies, education, becoming, creation, existences and coexistences. Flying with the bees that suffer from the ruins of the Anthropocene, we think of the honey beings, in its relationship with the environment going beyond the bee-flower-honey-fruit relationship. Literally cartographic, bees relate to the world in an endless rhizome of connections. Bees adapt and create ways to (re)exist amidst ruined landscapes. Affected by plantations, we created refuges from photographs, embroidered photographs to provoke thoughts connecting philosophy, biology and art. Creating landscapes in dialogues with Anna Tsing, we created refuges with embroidered photographs with the intention of surviving and (re)existing in the Anthropocene. These creations enabled us, amidst the ruins, to think about education in a multispecies perspective. A multispecies education based on affect, affecting and being affected, creating possibilities for coexistence and (re)existence.